Effects of Shaft Grouting on the Bearing Behavior of Barrette Piles: A Case Study in Ho Chi Minh City - Nguyen, P. H. V.; Nguyen, P. C. (Engineering, Technology & Applied Science Research, 2021)
The shaft-grouted method has been applied on high-rise buildings in Ho Chi Minh City for the purpose of increasing the bearing capacity of barrette piles. The Exim Bank Building foundation, using two kinds of shaft-grouted barrette piles, was 65m (TP1) and 85m (TP2) in depth. To assess the bearing capacity, this project assembly used the O-cell tools installed at 49m depth below the pile head level. Shaft grouting was performed from -25m to the TP1 pile toe level and -65m to the TP2 pile toe level. This work is based on the data from the O-cell experiments at the construction site and the results of finite element simulation in Plaxis software. The effectiveness of shaft grouting was analyzed and the length and position of the ejector were evaluated and compared in order to find the best solution for applying shaft grouting with the aim to ensure safety and mitigate economic problems.